2015
DOI: 10.1111/jicd.12184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green tea (Camellia sinensis) mouthwash containing 1% tannin on dental plaque and chronic gingivitis: a double‐blinded, randomized, controlled trial

Abstract: The 1% tannin green tea mouthwash could be a safe and feasible adjunct to mechanical plaque control. The tested green tea mouthwash could be considered a good alternative for chlorhexidine in contraindicating situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Also, there can be an idiosyncratic reaction of oral mucosal desquamations and soreness after the use of CHX [55]. Mouthwashes containing herbal extracts were investigated to have less or even no staining effect [58,59]. Based upon the existing evidence, no significant differences in the effects on plaque or gingivitis were observed between herbal and CHX mouthwashes.…”
mentioning
confidence: 99%
“…Also, there can be an idiosyncratic reaction of oral mucosal desquamations and soreness after the use of CHX [55]. Mouthwashes containing herbal extracts were investigated to have less or even no staining effect [58,59]. Based upon the existing evidence, no significant differences in the effects on plaque or gingivitis were observed between herbal and CHX mouthwashes.…”
mentioning
confidence: 99%
“…Unlike synthetic antiseptics, this plant extract was able to reduce fungal and bacterial biomass in vivo, despite the fact that it was neither fungicidal nor bactericidal in vitro [51][52][53]. This result suggests that SV extract could be able to preserve protective oral biofilm [41]. In Table 1, comparison of species-specific microbial load from baseline (D0) to D14 and from baseline to D28 confirmed a synergy between S. mutans and C. albicans previously described by Falsetta et al in 2014 [12].…”
Section: Discussionmentioning
confidence: 92%
“…Due to the chemical complexity of plant extracts, the exact role of major plant components or synergies between plant components still remains in question. However, several clinical studies demonstrated the efficacy of various herbal extracts to reduce plaque deposits and to improve oral conditions such as chronic gingivitis and post-operative dental surgery [39][40][41]44]. The review of literature revealed that vitamins and antioxidants of vegetal origin could interfere with inflammatory reaction, free radicals and endothelin in damaged periodontal tissues [17][18][19]48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This additional effect on biofilm removal could not be demonstrated with dental floss, wooden toothpicks, or oral irrigators . Obstacles to help explain the lack of clinical effectiveness of mechanical biofilm control for the majority of patients are numerous, and include limited time of use, lack of motivation, poor manual dexterity, tooth crowding, and tooth alignment …”
Section: Introductionmentioning
confidence: 99%